Citizen Lawsuit: A Tool for Public Control over the Fulfillment of Constitutional and Human Rights - Valencia, Yola; Gina Cahyani Zamri; Firli Adilla Sari; Jihan Alyani Dirayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
A citizen lawsuit is a legal instrument that allows individuals or groups to hold the government accountable for actions or policies deemed to violate human and constitutional rights. In the Indonesian legal system, although not explicitly regulated by law, this practice has developed through court decisions and the active role of civil society in demanding justice. This article aims to analyze the status, function, and urgency of strengthening the citizen lawsuit mechanism in defending public rights violated by the state. The method used is a normative juridical approach, examining legal literature, court decisions, and relevant regulations from the past five years. The results of the study indicate that citizen lawsuits not only serve as a means of correcting government policies but also play a crucial role in strengthening the principles of the rule of law, accountability, and participatory democracy.